Aktivitas Ekstrak Kunyit Hitam (Curcuma caesia) Terhadap Penyembuh Luka Sayat Pada Model Hewan Diabetes yang Diinduksi Aloksan - Bellatry Maharani; Inaratul Rizkhy Hanifah; Tri Wijayanti (JCPS (Journal of Current Pharmaceutical Sciences), 2025)
Black turmeric (Curcuma caesia) influences the wound healing process in male white Wistar rats suffering from diabetes with a focus on the anti-inflammatory content it contains. This study aimed to determine the activity of varying concentrations of black turmeric extract (Curcuma caesia) in healing diabetic wounds in a male white rat model involving 6 treatment groups, namely the no treatment group, the positive control group (bioplacenton gel), the negative control group (Na-CMC), groups varying the dose of black turmeric extract, namely 10%, 15%, 20%. The incision is applied and then smeared with the test preparation for up to 14 days in the morning and evening. Wound healing is measured by monitoring healing time and reduction in wound size. Data were analyzed statistically using the One Way ANOVA method. The study results showed that black turmeric extract could heal diabetic wounds in male white rats with an increase in the concentration of black turmeric, namely black turmeric extract containing 20%.